Theological Motivation and the Mutqin Method in Qur’anic Memorization: A Case Study of Manhalun Nabighin - Zamzila, Khairani; Rambe, Uqbatul Khair (Jurnal Pemikiran Islam, 2025)
This study investigates the integration of theological motivation and structured pedagogical practice in Qur’anic memorization (tahfidz) at Manhalun Nabighin, with a particular focus on the implementation of the Mutqin method. Employing a qualitative, phenomenological approach, data were collected from one program coordinator and thirteen students through in-depth interviews, non-participant observation, and analysis of institutional documents. The findings reveal that effective tahfidz at Manhalun Nabighin is grounded in a holistic educational paradigm, where memorization is not merely a technical pursuit but is embedded in spiritual values—such as ikhlas (sincerity), istiqamah (steadfastness), and an akhirah-oriented mindset—reinforced through daily routines, role modeling, and a supportive dormitory environment. The Mutqin method, characterized by systematic repetition (muraja’ah), rigorous evaluation, and peer support, fosters not only memorization quality and discipline but also emotional resilience and a lifelong commitment to the Qur’an. However, the research also highlights the dynamic nature of motivation, which is shaped by personal, familial, and technological challenges. The absence of formal psychosocial support points to the need for more comprehensive mentoring frameworks. These results underscore the importance of integrating theological motivation with adaptive pedagogical strategies to ensure sustainable and meaningful Qur’anic memorization. The study concludes with recommendations for educators and policymakers to develop holistic, context-sensitive tahfidz programs, and suggests future research to further examine comparative models and long-term outcomes.